The Effect of Economic Literature and the Amount of Pocket Money on Students Consumption Behavior Through Self Control - Marlisa Marlisa; Mahkdalena Mahkdalena; Gimin Gimin (Universitas Riau, 2021)
This study aims to determine and analyze the effect of economic literacy and the amount of pocket money on students consumption behavior through self-control. This type of research is descriptive quantitative. The types of research data are primary data and secondary data. The population in this study was 899 students majoring in social studies and a sample of 244 students. The sample uses Arikunto's opinion with a percentage of 25%. Data collection techniques in this study were tests and questionnaires. The data analysis technique in this study used SPSS 25. The results of this study show that Economic literacy and the amount of pocket money have a positive and significant effect on the self-control of students in the Social Sciences Major State Senior High School in Bagan Sinembah District. Economic Literacy and the amount of pocket money have a negative and significant effect on the consumption behavior of students in Social Sciences majoring SMA Negeri in the Bagan Sinembah. This proves that the better the economic literacy, the wiser and more rational in consumption will be and through the self-control that exists in students, especially it will help students in managing their pocket money.